Ensino de inglês para crianças em fase de alfabetização durante uma pandemia: desafios para a adaptação e elaboração de materiais didáticos - Erlo, Daniela Lopes (2021)
The main objective of the research is to characterize a context of teaching English to children and discuss some aspects related to the planning, implementation and evaluation of activities during the COVID-19 pandemic. This is the teaching context for a group of 9 students in the literacy phase of a private school in the countryside of São Paulo, where the teacher-researcher has been working for 12 years. We start from the assumption that the children in the preschool phase arrive at the school with a linguistic and cultural repertoire built mainly in their social interactions with the family and their circle of friends, because "learning and development are interrelated from the first day of a child’s life" (VIGOTSKY, 1998, p. 110). Therefore, the teacher plays a fundamental role in the context of formal education, when planning and implementing teaching situations that can contribute to social interaction between students and between students and materials. In addition, we start from the classification of scaffolding types proposed by Wood, Bruner and Ross (1976) from the Vigotskyan theory as categories of analysis of our corpus, considering that the didactic strategies used by the teacher are types of scaffolding to be offered to the students in the performance of activities in groups, in pairs or individual. As a result, our research identified that, in the context, a printed educational material is used that bases the teaching planning, based on the principles of integration, autonomy, independence and access to culture. In addition, our analyses showed that the process of teaching English language learning in the literacy phase, based on activities that promote interactions in a cooperative approach (DONNINI, 2013) could contribute to greater involvement of families in the mediation process, which was fundamental for the teaching and learning of the English language in the researched context.